ANALISIS PENGARUH MEDIA PEMBELAJARAN TERHADAP PERKEMBANGAN KEPRIBADIAN SISWA DI ERA DIGITAL - Ifan Hakim (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This article discusses the influence of instructional media on the development of students' personalities in the context of the digital and millennial era. Online learning media, social media, mass media, and audiovisual instructional media have significant effects, both positive and negative. While providing ease of access and expanding students' horizons, the use of these media also has the potential to create negative impacts such as laziness, decreased social interaction, and dependence on technology. This research utilizes a descriptive qualitative method to understand phenomena occurring in students. The importance of the teacher's role in effectively managing the use of instructional media to maximize its benefits in the learning process is also highlighted. In the context of online learning, challenges such as lack of teacher supervision and dependence on gadgets are also discussed. In conclusion, the use of instructional media must be carefully considered to ensure balanced and positive development of students' personalities.